Fresno County Bar Association Law Day Luncheon with U.S. Attorney David Levy at Fresno Hilton Ballroom - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy, U.S. Attorney David Levy, and Lawrence O'Neill